AN IMPROVEMENT OF THE APPLIED SKILLS OF PRACTICAL SHOOTING IS IN SYSTEM OF TRADE EDUCATION OF NATIONAL POLICE OF UKRAINE - Morgunov, О. А.; Yareshchenko, О. А.; Khatsayuk, О. V. (Honor and Law, 2019)
In the scientific article the issue of the day of professional preparedness of policemen of the National police of Ukraine is examined in accordance with the requirements of present time. Modern methodology of improvement of skills of the practical shooting is exposed by facilities of the special physical preparedness. The participants of pedagogical experiment are get practical skills of the battle firing for providing of implementation of tasks fixed on the National police of Ukraine.